VAT cuts as emergency policy intervention: Evidence from the UK case - Luisanna Onnis; Claudio A. Piga; Maurizio Conti; Anna Bottasso (Cardiff University, Cardiff Business School, 2025)
In July 2020, the UK government reduced the VAT rate on hospitality services from 20% to 5% as an emergency policy intervention. Using a novel dataset of detailed hotel room characteristics in UK and elsewhere, we estimate how much the tax cut was passed on to consumers via a price reduction. We find a statistically significant contemporaneous pass-through to hotel room prices that varies between around 20% and 50%, with a peak effect on prices observed on the second week after the reform. However, the pass-through effect is the outcome of a discretionary approach as discounts were negligible for rooms sold two months after the policy introduction.
Keywords: H22; H25; L83; 330; VAT cut; pass-through; hospitality